2006
DOI: 10.1007/s00467-006-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and copper levels in children with chronic renal failure

Abstract: Chronic hemodialysis may lead to abnormalities in the serum levels of some trace elements in children with CRF that increase in severity with increasing duration of hemodialysis. Deficiencies of these trace elements--zinc in particular--may contribute to various conditions and symptoms in children undergoing chronic hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…According to previous studies, [1][2][3][4][5] our data also demonstrated Zn deficiency in HD patients. In addition, our study demonstrated for the first time, a correlation between this deficiency with high TNF-α and LDL(-) levels in HD patients, suggesting the crucial role of Zn as an antioxidant in these patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to previous studies, [1][2][3][4][5] our data also demonstrated Zn deficiency in HD patients. In addition, our study demonstrated for the first time, a correlation between this deficiency with high TNF-α and LDL(-) levels in HD patients, suggesting the crucial role of Zn as an antioxidant in these patients.…”
Section: Discussionsupporting
confidence: 80%
“…In patients with chronic kidney disease (CKD), the Zn deficiency is common as a result of uremia, reduced renal function, diet, medication, losses in dialysis treatment, and an impaired absorption of Zn through the intestine. [1][2][3][4][5] Due to the biological importance of Zn as an antioxidant agent, its deficiency could contribute to the development of atherosclerotic cardiovascular (CV) disease in CKD patients. 6 In this sense, the deficiency of antioxidants in these patients has been associated with increased oxidative stress, and can be involved in the generation of a pro-apoptotic subfraction of LDL, called electronegative LDL [LDL (-)].…”
Section: Introductionmentioning
confidence: 99%
“…During dialysis some trace elements can accumulate in the body because of dialysis fluid impurities, and others may move from blood to the dialysate, leading to deficiency of some trace elements [11]. Also, the distribution of trace elements can be affected by insufficient dietary intake, degrees of gastrointestinal absorption, and drug treatment, and it can lead to some clinical abnormalities in uremic patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium, copper, chromium, lead and mercury are some of the more common effluent pollutants discharged from industries which causes a number of hazardous diseases. So there is a very urgent need to control heavy metal emissions into the environment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%